An exploration of the lived experiences of social workers dealing with victims of intimate partner violence at Ehlanzeni District, Mpumalanga - Mhlongo, Lindokuhle Angelo (My University, 2019)
Intimate partner violence (IPV) poses a major challenge for social workers worldwide, as well as in South Africa. In light in the above, the present study aimed to explore the lived experiences of social workers dealing with victims of IPV at Ehlanzeni District, Mpumalanga Province. A qualitative study was conducted among social workers working with victims of IPV. The study had anticipated using 10 participants but, due to data saturation, only six participants were interviewed. Each interview took 45–60 minutes, depending on each participant’s responses. A total of six participants, all females between the ages of 24 and 39 years, were selected using purposive sampling. The data were collected using semi-structured interviews, and interpretive phenomenological analysis (IPA) was applied for data analysis. Four major themes emerged from the analysis of the data: a) emotional and psychological distress experienced by social workers; b) impact on personal and professional lives; c) coping strategies; and d) vicarious posttraumatic growth. Importantly, some themes and subthemes not included in the interview guide emerged from the data. These included subthemes such as family involvement and societal pressure. The findings of the study highlighted that it is quite rare for men to report IPV, although at times they do. There is greater IPV prevalence among females of different ages. Secondary traumatisation is one of the negative effects that social workers experience when working with cases of traumatic IPV. However, social workers have found effective ways of coping with the demands of their work. Some of the identified coping mechanisms included choosing to spend time with family, trying to forget about the day’s work, travelling, being strong and resilient, consulting a psychologist, playing games, praying (spirituality) and reading the Bible, sharing their experiences with a more experienced social worker, spending time with friends, laughing, singing and remaining professional. The study found that these coping strategies helped the social workers to deal with burnout and compassion fatigue. The present study recommends that effective coping methods and support for mental health care workers are needed to assist with secondary trauma stress and the negative effects that comes with the job.
Thesis (M.A. (Clinical Psychology)) -- University of Limpopo, 2019
Keywords: Intimate partner violence (IPV); Social workers; Family violence -- South Africa -- Mpumalanga; Social workers -- South Africa -- Mpumalanga; Intimate partner violence